Effect of human disturbances and hydrologic elements on the distribution of plant diversity within the Shamu watershed, Mt. Yuntai Nature Reserve, China. (1st June 2022) - Li, Chaojun; Lou, Hezhen; Yang, Shengtian; Li, Xi; Zhang, Jun; Pan, Zihao; Zhang, Yujia; Yi, Yin; Gong, Jiyi
Abstract: This paper explores how human disturbance and hydrologic elements affect the spatial distribution pattern of plant diversity in the watershed, taking Shamu watershed in the World Natural Heritage Site as a case study. Spatial analysis of multisource remote sensing and plant diversity plots data were conducted using linear mixed effects models and structural equation models. Results revealed that the distribution of plant diversity in the watershed is mainly affected by human disturbance. However, under similar human disturbance levels, hydrologic elements also affect the plant diversity within the watershed. The topographic undulation and surface runoff significantly promote plant diversity, while the river network density, the watershed shape factor, the river longitudinal gradient do not. The influence of topographic undulation is more obvious than that of runoff on plant diversity, but the effect of topographic undulation and runoff on plant diversity is getting weaker from upstream to downstream within the watershed. In addition, the impact of hydrologic elements on plant diversity is mainly regulated by environmental factors Pre and Tem. The findings clarify how human disturbance and hydrologic elements affect plant diversity distribution within the watershed, optimizing the conservation theory of plant diversity resources and scientifically guiding the region's sustainable development. Highlights: Human disturbance contributes most to plant diversity. Surface runoff and topographic undulation promote plant diversity. Precipitation and temperature regulate the hydrological impact on plant diversity. Weaker restrictions of hydrologic elements on plant diversity in downstream.